Behavioral deviance of some women in the Middle Maghreb during the Middle Ages - ouadi, lamia (The Algerian Historical Journal, 2026)
This study addressed the issue of some women’s behavioral deviance in the Islamic Maghreb, which has resulted from a variety of internal and external interactions that have led some them to practice this behavior. The latter appeared in women’s daily lives, both inside and outside the family, in several images and forms, having a negative impact on the family environment in particular and society in general. Several parties - judges and jurists - had tried to contain them and counter their deviant behavior, but their efforts had not reached the desired goal, some of which had been intractable